Pengaruh Kualitas Pelayanaan Terhadap Kepuasaan Nasabah Di Bank BJB Cabang Buah Batu - Barus, Camelia Br; Muthmainnah, Muthmainnah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The research aims to determine the effect of customer satisfaction. The research method uses quantitative methods and the resulting sample is 212 respondents. By using a simple regression analysis test using the SPSS 2022 tool. The results for this study, on service quality customer satisfaction with a coefficient of determination of 81.2%.